Mikroenkapsulasi Mineral Besi dan Seng dalam Pembuatan Makanan Tambahan untuk Balita Gizi Kurang - Lilik Kustiyah; Faisal Anwar; Mira Dewi (Institut Pertanian Bogor, 2011)
As a health problem, prevalence of severe underweight in Indonesia is still high. Riskesdas 2008 indicate that prevalence of severe underweight and underweight in Indonesia are 5.5% and 13.0%, respectively. Effort to overcome that problem are still focused on severe underweight children, so need to anticipate of getting worse of underweight ones of being fell into severe underweight. The aim of this research is to make RUF fortified by encapsulated iron and zinc to overcome underweight balita (under five of age children). First step of this research is making flour from rice, soybean, cassava, sweet potato and taro with proceeded by two kinds of treatment, i.e. physic method (using high temperature and pressure) and soaking in solution of Na2HC03 (1.5% and 2.0%). Drum dryer was applied to dry the ingredient (rice, soybean, cassava, sweet potato and taro) and then milled using disc mill. Microencapsulation of iron and zinc was using arabic gum and maltodextrin (80:20 and 70:30) and concentration of iron or zinc each is 5.0% and 7.5%. Then, assays of stability of microencapsulated iron and zinc, and their bioavailability (in vitro and in vivo). Before mixed with minerals, 12 combinations of flour (3 kinds of tuber x 2 cooking time x 2 concentration of Na2C03) are tested by hedonic test to choose the best preferences of that combination of ingredients of porridge. Based on technical, economical, and technological considerations, and acceptability, mixed of rice, soybean, and sweet potato is selected as based ingredients of porridge. There is no color and odor change or even crystalline forming during more than one month of storing of microencapsulated iron and zinc. Bioavailability (in vitro) of Fe is around 15,48% to 17,05% and Zn is around 6.05% to 6,36%.